Knowledge of nutritionists on the management of type 1 Diabetes mellitus regarding macronutrient counts and insulin units (Research, Society and Development, 2023)
Type 1 Diabetes mellitus is a metabolic disorder characterized by the destruction of pancreatic β-cells through an autoimmune response, generating a deficit in insulin synthesis that results in hyperglycemia and requires insulin-based treatment. Carbohydrate counting is the most efficient method for glycemic control and calculating insulin per meal. The objective of this work was to evaluate the knowledge of nutritionists graduating from UFV/CRP on the management of this type of diabetes in terms of counting macronutrients and insulin units. The exploratory and descriptive study was carried out using a questionnaire prepared in Google Forms, containing questions for the general description of those evaluated and 10 questions to assess the level of knowledge. Data are presented in absolute and relative frequencies. As for knowledge, 54.54% were rated good, and only 3.03% were rated bad. In the distribution of points, the majority presented scores between 7 and 9 points, with none of the participants obtaining scores 1, 2 and 10. It is concluded that the majority of participants had knowledge about the management of this pathology in terms of counting macronutrients and insulin units, however, the need for training such as lectures and mini-courses for this audience is justified, as some people got some basic and specific questions wrong on the subject.